Fructose rich alternative carbon sources for enhanced fossil fuels biodesulfurization - Silva, Tiago (2014)
Biodesulfurization allows the removal of recalcitrant sulfur from fossil fuels at mild operating conditions with the aid of microorganisms. However the production of biocatalysts still has elevated costs which hinder its industrial application. So the use of agro-industrial by-products and wastes, as alternative carbon sources could present an opportunity to cheapen the process. In previous works we showed that Gordonia alkanivorans strain 1B has the ability to use materials such as recycled paper sludge hydrolysate and carob pulp liquor to grow and desulfurize after some optimization. Since this is a fructophilic bacterium it is important to compare the use of carbon sources progressively richer in fructose.